Rereading Comboni’s Plan for the Regeneration of Africa in the Light of Today’s Africa - Ozioko, Johnson Uchenna (Alpha Omega, 2016)
Summary: The hundred and fiftieth anniversary of Daniel Comboni’s Plan for the Regeneration of Africa offered a propitious occasion for reflection on the enduring relevance of Comboni’s project for the Church’s evangelizing mission especially in Africa. Beginning with a documentation of the historical context within which Comboni articulated his Plan, the essay tried to situate the Plan in its context. Analysing the present circumstances of Africa, it concentrated on articulating some elements which highlight the conditions necessary in order that Comboni’s Plan might maintain its relevance in today’s Africa. Key Words: Africa, Daniele Comboni, Church, Mission, Missionary Spirituality, Incultura-tion, Evangelization. Sommario: Il centocinquantesimo anniversario del Piano per la rigenerazione dell’Africa di Daniele Comboni ha offerto una occasione favorevole per una riflessione sulla attualità per-manente del progetto per la missione evangelizzatrice della Chiesa soprattutto in Africa. Par-tendo con una documentazione del contesto storico nel quale Comboni articolò il suo Piano, il saggio ha cercato di situarlo nel suo contesto. Analizzando le circostanze attuale dell’Africa, si è soffermato ad articolare alcuni elementi che mettono in evidenza le condizioni necessarie perché il Piano di Comboni potesse mantenere la sua attualità nell’Africa di oggi. Parole chiave: Africa, Daniele Comboni, Chiesa, Missione, Spiritualità missionaria, Incultu-razione, Evangelizzazione.